Absence of Nrf2 or Its Selective Overexpression in Neurons and Muscle Does Not Affect Survival in ALS-Linked Mutant hSOD1 Mouse Models - Vargas, Marcelo R. (Public Library of Science, 2013)
The nuclear factor erythroid 2-related factor 2 (Nrf2) governs the expression of antioxidant and phase II detoxifying enzymes. Nrf2 activation can prevent or reduce cellular damage associated with several types of injury in many different tissues and organs. Dominant mutations in Cu/Zn-superoxide dismutase (SOD1) cause familial forms of amyotrophic lateral sclerosis (ALS), a fatal disorder characterized by the progressive loss of motor neurons and subsequent muscular atrophy. We have previously shown that Nrf2 activation in astrocytes delays neurodegeneration in ALS mouse models. To further investigate the role of Nrf2 in ALS we determined the effect of absence of Nrf2 or its restricted overexpression in neurons or type II skeletal muscle fibers on symptoms onset and survival in mutant hSOD1 expressing mice. We did not observe any detrimental effect associated with the lack of Nrf2 in two different mutant hSOD1 animal models of ALS. However, restricted Nrf2 overexpression in neurons or type II skeletal muscle fibers delayed disease onset but failed to extend survival in hSOD1(G93A) mice. These results highlight the concept that not only the pharmacological target but also the cell type targeted may be relevant when considering a Nrf2-mediated therapeutic approach for ALS.